A Few Thoughts on the Social Inertia of Countries in transition - Polšek, Darko (Array, 1997)
Despite the generally accepted will of Eastern European citizens to become part of the Western world, the transformations of Eastern European societies are far from uniform and the processes taking place in these countries present a real challenge.